Expansion planning studies of generation sector in highly renewable energy systems considering flexibility requirements - Kianoosh Choubineh; Hossein Yousefi; Moein Moeini-Aghtaie (International Journal of Electrical Power & Energy Systems, 2025)
This work focuses on the development of a decarbonization-based generation expansion planning (GEP) model taking into account short-term operational constraints. In this planning model, two different criteria are developed to properly evaluate the relationship between the CO2 emissions in generation sector of renewable-based power systems and the flexibility requirements. Mixed integer linear programming method is deployed to run the decarbonization-based GEP model proposed in this work. Also, to develop the decarbonized power system, CO2 emissions cost is incorporated into the objective function of the model, and flexibility sufficiency of the power system is ensured using integration of short-term operational requirements in the model. Results show that applying the CO2 emissions cost in the objective function of expansion planning studies lead to changes in generation mix and significantly increases the penetration of renewables in the power system. Also, the implementation of stringent approaches, such as the immediate prohibition of flexible generation units expansion, does not lead to effective results in reducing CO2 emissions throughout the planning horizon. Finally, banning the development of flexible generation units, significantly increases the risk of lack of flexibility in the power system.